ANALISIS STRUKTUR MIKRO DAN SIFAT MEKANIS HASIL LAS TITIK DAN BRAZING UNTUK INDUSTRI RUMAHAN - Deivandra Ginanjar Bhakti; Gunawan Dwi Haryadi; Yusuf Umardani (JURNAL TEKNIK MESIN, 2013)
In the welding process there are several factors that determine the success of welding. The alteration of microstructure of joined metals are expected to change the structure of the material into more dense to make connections become stronger. In this study, the material used is ferrous steel plate with a maximum thickness of 1mm. In order to know the results, It required to use some variation of a parameter such as pressing time and plate thickness used for metal welding process. The process used home brazing welding machine, the connections are welded and welding receive local heat and during the process the temperature is constantly changing so that the temperature distribution is uneven. As a result of this stretch then analyzed the results of the micro structure of the welding process using brazing home welding machine. After analysis of the microstructure was done then analyze the mechanical properties of the weld joint, all this analysis needs to be done in order to ascertain the connection is really strong welds and brazing machine can be used for home-scale cottage industry.  The results of this study indicate that nugget on hardness Vickers test has a value higher than of the base metal which is 172.78 for 8.6 A current and welding time 20 second 191.58 for 6 A current and welding time of 10 second, and the value of base metals 165.7 so percentage obtained with increasing force to the current value of 8.6 A is 7.1 % and for the current 6 A 25.8 %